DIAGNOSIS OF FETAL ANASARCA BY REAL TIME ULTRASONOGRAPY IN A PUG BITCH AND ITS SURGICAL MANAGEMENT - SRIDEVI, P; REENA, D; SAFIUZAMMA, M (The Indian Journal of Animal Reproduction, 2016)
Real time ultrasonography revealed increased subcutaneous edema and serous effusions in a fetus in utero, thus diagnosing the cause of dystocia in a Pug bitch as fetal anasarca. In brief, ultrasonography is an excellent option to diagnose the cause of dystocia in canines and caesarean section can be planned to improve the prognosis of the case.
Keywords: Dog; Fetal anasarca; Hydrops fetalis; Pug; Ultrasonography